470 Maternal Habitual Snoring and Blood Pressure Trajectories in Pregnancy. (3rd May 2021) - Dunietz, Galit Levi; Hao, Wei; Shedden, Kerby; Holzman, Claudia; Chervin, Ronald; Lisabeth, Lynda; Treadwell, Marjorie; O'Brien, Louise
Abstract: Introduction: Habitual snoring has been associated with hypertensive disorders of pregnancy. However, exactly when blood pressure (BP) trajectories diverge between pregnant women with and without habitual snoring is unknown. Moreover, the potentially differential impact of chronic versus pregnancy-onset habitual snoring on maternal BP trajectories during pregnancy has not been examined. Methods: In a cohort study of 1, 305 pregnant women from a large Midwestern medical center, participants were asked about habitual snoring (≥3 nights/week) and whether their symptoms began prior to or during pregnancy. Demographic and BP data throughout pregnancy, systolic (SBP) and diastolic (DBP) were abstracted from medical charts. Linear mixed models were used to examine associations between habitual snoring-onset and pregnancy BP trajectories. Results: Thirty percent of women reported snoring before pregnancy (chronic snoring) and an additional 23% reported pregnancy-onset snoring. Overall, women with pregnancy-onset snoring had higher mean SBP and DBP compared to those with chronic habitual snoring or controls (non-habitual snoring). In gestational week-specific comparisons with controls, SBP became significantly higher around 20 weeks' gestation among women with pregnancy-onset snoring and in the third trimester among women with chronic snoring. Pairwise mean differences in DBP were significant only among women with pregnancy-onset snoring relative to controls, after 15 weeks' gestation. Conclusion: In a large cohort of pregnant women, those with pregnancy-onset or chronic habitual snoring had significantly elevated systolic BP in comparison to non-habitual snoring controls, in the second and third trimester, respectively. The findings of divergent BP trajectories suggest the two groups of women with habitual snoring in pregnancy should be considered separately when evaluating gestational 'windows' for increased BP monitoring and provide insight into pathophysiologic changes. Support (if any): Dr. Dunietz was supported by an F32 National Research Service Award from the National Institute of Child Health and Development (NIH/NICHD F32 HD091938); Dr. O'Brien was supported by the following during the course of this study: the Gene and Tubie Gilmore Fund for Sleep Research, the University of Michigan Institute for Clinical and Health Research (MICHR) grants UL1RR024986 and UL1TR000433, MICHR seed pilot grant F021024, the National Heart, Lung, and Blood Institute (R21 HL089918 and K23 HL095739) and in part by R21 HL087819.